Studi Variasi Gelling Agent PVA (Propil Vinil Alkohol) pada Formulasi Masker Peel-Off Ekstrak Lidah Buaya (Aloe vera) sebagai Anti Jerawat - Dias Ardini; Pudji Rahayu (Politeknik Kesehatan Tanjung Karang, 2019)
Gel mask can increase skin moisture and enhance the effect of the main composition (Aloe vera L) as an anti-acne on the epithelial and that is the cause of occlusivity of the polymer layer formed. PVA formulation is used to give exfoliated effect because they have adhesive properties or can form films that are easily peeled off after drying. The purpose of this study was to determine the effect of polyvinyl alcohol (PVA) variations as a gelling agent (7%, 10%, 13% and 16%) on the physical properties of ethanol extract Aloe vera leaves skin gel mask included organoleptic, homogeneity, pH, dispersibility, drying time and inhibition test against Staphylococcus epidermidis. The research conducted is experimental. The design of this research is a one-shot case study. Evaluation results were analyzed using univariate analysis. For physical properties, frequency distribution and inhibitory tests were analyzed with Analysis of variance (ANOVA). Peel off gel mask is formulated with 4 treatments and 6 repetitions. The results showed that the peel-off gel mask of Aloe vera leaves ethanol extract have clear organoleptic properties, very weak alcohol flavor and 50% slightly thick and 25% thick and 25% very thick. 75% of mask preparations are homogeneous. Has a pH range of 5.95-6.2. The spreadability of 75% gel mask preparations are meet the requirements of mask masking and 75% meets the requirements of good drying time. All variations of the formula have an inhibition effect against Staphylococcus epidermidis and between training groups, no difference was understood.